Minimally invasive valve sparing aortic root replacement (David procedure) is safe - Shrestha, Malakh; Krueger, Heike; Umminger, Julia; Koigeldiyev, Nurbol; Beckmann, Erik; Haverich, Axel; Martens, Andreas (Annals of Cardiothoracic Surgery; Vol 4, No 2 (March 29, 2015): Minimally Invasive Aortic Valve Surgery (II), 2014)
Objectives: Even though minimally invasive cardiac surgery may reduce morbidity, this approach is not routinely performed for aortic root replacements. The purpose of this pilot study was to assess the safety and feasibility of valve sparing aortic root replacement via an upper mini-sternotomy up to the 3rd intercostal space. Methods: Between April 2011 and March 2014, 26 patients (22 males, age 47.6±13 years) underwent elective minimally invasive aortic valve sparing root replacement (David procedure, group A). Twelve patients (11/26) underwent additional leaflet repair. Concomitant procedures were: four proximal aortic arch replacements and one coronary artery bypass grafting (CABG) to the proximal right coronary artery (RCA). During the same time period, 14 patients (ten males, age 64.2±9.5 years) underwent elective David procedure via median full sternotomy (group B). Concomitant procedures included six proximal aortic arch replacements. Although the patient cohorts were small, the results of these two groups were compared. Results: In group A: there were no intra-operative conversions to full sternotomy. The aortic cross-clamp and cardiopulmonary bypass (CPB) times were 115.6±30.3 and 175.8±41.9 min, respectively. One patient was re-opened (via same access) due to post-operative bleeding. The post-operative ventilation time and hospital stay were 0.5±0.3 and 10.4±6.8 days, respectively. There was no 30-day mortality. The patient questionnaire showed that the convalescence time was approximately two weeks. In group B: the cross-clamp and CPB times were 114.1±19.9 and 163.0±24.5 min, respectively. One patient was re-opened (7.1%) due to postoperative bleeding. The post-operative ventilation time and hospital stay were 0.6±0.7 and 14.2±16.7 days, respectively. There was no 30-day mortality. Conclusions: Minimally invasive valve sparing aortic root replacement can be safely performed in selected patients. The results are comparable to those operated via a full sternotomy. The key to success is a ‘step by step’ technique of moving from minimally invasive aortic valve replacements (AVR) to more demanding aortic root replacements. Meticulous hemostasis & attention to surgical details is of utmost importance to prevent perioperative complications.